The Impact of Gamified Interventions on Youth Health Literacy: A Systematic Review of Effectiveness and Implementation Challenges - Zikra, Andi Anzanul (Yayasan Sinergi Kawula Muda, 2023)
Educational games have emerged as effective tools to improve health literacy among children and adolescents, significantly impacting knowledge acquisition, behavior modification, and long term health outcomes. This narrative review systematically examines existing literature to evaluate the effectiveness of gamified interventions designed for youth health education. A structured literature search was conducted across major academic databases, including Scopus, PubMed, and Google Scholar, using targeted keywords and stringent inclusion and exclusion criteria. Findings indicate that gamification enhances learning engagement and sustains motivation, particularly in mental health literacy, nutrition education, physical activity promotion, and chronic disease management. Despite consistent evidence supporting their effectiveness, systemic issues such as limited technological infrastructure, cultural stigmatization, varying degrees of governmental and educational policy support, and differing accessibility across socio economic contexts significantly moderate outcomes. Discussion highlights the critical role of contextually relevant, user centered game design and emphasizes the necessity of robust infrastructural investments, policy reforms, and professional development for educators. Future research directions recommend longitudinal studies to evaluate sustained impacts, cross cultural comparative analyses, and economic feasibility assessments. Ultimately, the strategic implementation of educational games, supported by strong multi sector collaboration, presents considerable potential to bridge global health literacy gaps, underscoring the urgency for continued development and refinement in gamified health interventions.